The Raising Of Predicates : Pedicative Noun Phrases And The Theory Of Clause Structure - MORO, Andrea (Cambridge studies in linguistics ;, 1997)
One of the basic premises of the theory of syntax is that clause structures can be minimally identified as containing a verb phrase, playing the role of predicate, and a noun phrase, playing the role of subject.